Draft Annual Plan 1988-89 Government of Karnataka - Planning Commission (Planning Commission, 1987)
The State's economy could only partially recover during 1986-87 from the crippling effects of the severe drought during 1985-86. During 1987-88 also, the hopes of complete recovery and satisfactory progress of development programmes in the direction of achieving the goals of the ’Seventh Five Year Plan are again jeopardised by persisting drought conditions in the State, in spite of the best efforts made to maintain the tempo of development activities, particularly relief measures to minimise the rigours of drought on the vulnerable sections of the society. The rain fall conditions during 1987-88 so far, have been none-too-good and were characterised by scarce pre-Monsoon showers, delayed onset of South-West Monsoons and long dry spells during crucial periods of crop growth.
Government of Karnataka Planning Department